2018
DOI: 10.1177/0735633117752453
|View full text |Cite
|
Sign up to set email alerts
|

Enhancing and Modeling Teachers’ Design Beliefs and Efficacy of Technological Pedagogical Content Knowledge for 21st Century Quality Learning

Abstract: This study proposed a new conceptualization of technological pedagogical content knowledge (TPACK) that focuses exclusively on the intersection of technology, pedagogy, and content specifically for selected dimensions of 21st century learning. In addition, teachers’ design beliefs were investigated with the teachers’ TPACK. Given the conceptualization, a new instrument was designed and validated. An associated intervention program to enhance the preservice teachers' TPACK was designed and the pre- and post-cou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
0
7

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 85 publications
(60 citation statements)
references
References 35 publications
2
51
0
7
Order By: Relevance
“…The ability to think critically, solve problems, be innovative, communicate, and collaborate are important competencies in entering the life of the 21 st century. The use of technology in the 21 st century's learning is in line with research conducted by Chai (2018) which shows that the 21 st century's learning is supported by technology and designs comprehensive skills to address the 21 st century technological challenges.…”
Section: Introductionsupporting
confidence: 69%
“…The ability to think critically, solve problems, be innovative, communicate, and collaborate are important competencies in entering the life of the 21 st century. The use of technology in the 21 st century's learning is in line with research conducted by Chai (2018) which shows that the 21 st century's learning is supported by technology and designs comprehensive skills to address the 21 st century technological challenges.…”
Section: Introductionsupporting
confidence: 69%
“…Future research directions might involve a bigger focus on many of the aspects that have been discussed in this study, including more emphasis on the examination of new instruments and theoretical frameworks, as well as how to adapt the specificities of social studies education in such models. For instance, it should be determined in the future whether alternative conceptualisations, such as the TPACK-21CQL model, which focuses on 21st century quality learning (Chai et al, 2019), are a better fit in the assessment of these competences.…”
Section: Limitations and Future Directionsmentioning
confidence: 99%
“…This application can ease and assist lecturers or instructors to know the competencies of the Pre-service teacher. Several studies showed the importance of increasing teacher professionalism in learning in various fields by utilizing technology emphasizing in pedagogical aspects (Ajmain et al, 2019;Anagun, 2018;Chai et al, 2019;Chou et al, 2018;Ismail et al, 2018;Tican, & Deniz, 2019;Van Hong et al, 2018). The results of those studies support the idea of developing an evaluation model for the pedagogic competence conducted in this study.…”
Section: Discussionmentioning
confidence: 99%